A climate-adapted push-pull system effectively controls fall armyworm, Spodoptera frugiperda (J E Smith), in maize in East Africa. (March 2018) - Midega, Charles A.O.; Pittchar, Jimmy O.; Pickett, John A.; Hailu, Girma W.; Khan, Zeyaur R.
Abstract: Fall armyworm, Spodoptera frugiperda (J E Smith), an economically important pest native to tropical and sub-tropical America has recently invaded Africa, causing substantial damage to maize and other crops. We evaluated functionality of a companion cropping system, 'climate-adapted push-pull', developed for control of cereal stemborers in drier agro-ecologies, as an added tool for the management of fall armyworm. The technology comprises intercropping maize with drought-tolerant greenleaf desmodium, Desmodium intortum (Mill.) Urb., and planting Brachiaria cv Mulato II as a border crop around this intercrop. Protection to maize is provided by semiochemicals that are emitted by the intercrop that repel (push) stemborer moths while those released by the border crop attract (pull) them. 250 farmers who had adopted the technology in drier areas of Kenya, Uganda and Tanzania were randomly selected for the study during the long rainy season (March-August) of 2017. Each farmer had a set of two plots, a climate-adapted push–pull and a maize monocrop. Data were collected in each plot on the number of fall armyworm larvae on maize, percentage of maize plants damaged by the larvae and maize grain yields. Similarly, farmers' perceptions of the impact of the technology on the pest were assessed using a semi-structured questionnaire. Reductions of 82.7% in average number of larvae per plant and 86.7% in plant damage per plot were observed in climate-adapted push-pull compared to maize monocrop plots. Similarly, maize grain yields were significantly higher, 2.7 times, in the climate-adapted push-pull plots. Farmers rated the technology significantly superior in reducing fall armyworm infestation and plant damage rates. These results demonstrate that the technology is effective in controlling fall armyworm with concomitant maize grain yield increases, and represent the first documentation of a technology that can be immediately deployed for management of the pest in East Africa and beyond. Highlights: Fall armyworm has invaded Africa, causing substantial damage to maize and other crops. There is no control method for this pest in Africa, and pesticides are only minimally used in the continent. Climate-adapted push-pull technology overcomes stemborers, some of which belong to the same family as the fall armyworm. On-farm data confirm effectiveness of the technology in control of fall armyworm in East Africa. This provides the first report of an effective management approach for the pest in the region and beyond.